Flapping about: trends and drivers of Australian cownose ray (Rhinoptera neglecta) coastal sightings at their southernmost distribution range - Chan, Alysha J.; Jaine, Fabrice R. A.; Maron, Francisca; Williamson, Jane E.; Schilling, Hayden. T.; Smoothey, Amy F.; Peddemors, Victor M. (Frontiers in Fish Science, 2024)
The Australian cownose ray (Rhinoptera neglecta) is an understudied batoid that occurs along Australia's north and east coasts. Currently classified as Data Deficient on the IUCN Red List of Threatened Species, major knowledge gaps exist regarding the species' geographic range, habitat use and the drivers influencing its presence in coastal Australian waters. Sightings of R. neglecta were collected during systematic aerial surveys conducted along 980 km (~47%) of the New South Wales (NSW) coastline between 2017 and 2019. North-bound surveys were flown 500 m offshore, whilst return surveys were flown along the beach/sea interface (inshore or nearshore). Using generalised additive models and a set of nine environmental predictors, we examined the relationship between the spatio-temporal occurrence of R. neglecta, their group size and the biophysical environment at the southernmost extent of their distribution. Results for the presence/absence (44.20% deviance explained) and group size of R. neglecta observed offshore and inshore (42.58% and 41.94% deviance explained, respectively) highlighted latitude, day of year, sea surface temperature, rainfall, wind speed and wind direction as common influences to the three models. The models indicated R. neglecta were more likely to be present in the northern half of NSW during spring and summer months. However, larger group sizes were more likely to be observed in more southern regions during the same seasons, regardless of whether they were observed offshore or inshore. Group size is also likely influenced by more localised conditions, such as SST and tidal flows. This study represents the largest attempt to date to decipher the spatial ecology of R. neglecta and provides insights into the spatio-temporal distribution and relative abundance of the species along the full extent of the NSW coastline, extending the species' known distribution by over 70 km southward.